Entomopathogenic and plant pathogenic nematodes as opposing forces in agriculture. Issue 1 (January 2016) - Kenney, Eric; Eleftherianos, Ioannis
Graphical abstract: Highlights: Entomopathogenic nematodes coexist with plant pathogenic nematodes. Nematodes interact with the immune systems of their respective hosts. Plant pathogenic nematodes suppress entomopathogenic nematodes. Factors from entomopathogenic nematodes can repel plant pathogenic nematodes. Novel strategies are required to control plant pathogenic nematodes in the field. Abstract: Plant-parasitic nematodes are responsible for substantial damages within the agriculture industry every year, which is a challenge that has thus far gone largely unimpeded. Chemical nematicides have been employed with varying degrees of success, but their implementation can be cumbersome, and furthermore they could potentially be neutralising an otherwise positive effect from the entomopathogenic nematodes that coexist with plant-parasitic nematodes in soil environments and provide protection for plants against insect pests. Recent research has explored the potential of employing entomopathogenic nematodes to protect plants from plant-parasitic nematodes, while providing their standard degree of protection against insects. The interactions involved are highly complex, due to both the three-organism system and the assortment of variables present in a soil environment, but a strong collection of evidence has accumulated regarding the suppressive capacity of certain entomopathogenic nematodes and their mutualistic bacteria, in the context of limiting the infectivity of plant-parasitic nematodes. Specific factors produced by certain entomopathogenic nematode complexes during the process of insect infection appear to have a selectively nematicidal, or at least repellant, effect on plant-parasitic nematodes. Using this information, an opportunity has formed to adapt this relationship to large-scale, field conditions and potentially relieve the agricultural industry of one of its most substantial burdens.